(untitled) (Bangladesh Journal of Livestock Research, 2020)
The study was conducted with the objective to investigate prenatal and postnatal performances of Red Chittagong Cattle (RCC) cows in subsistence feeding and nutrition compared to those in improved feeding system. Twenty RCC cows with average initial live weight of 204.6 (±29) kg at their 2nd or 3rd parity and at about seven months of pregnancy were divided into two equal groups and assigned to two dietary treatments: one group was fed as per farmers’ choice, while another was fed 25% higher metabolizable energy (ME) and crude protein (CP) than requirements through concentrates, according to ARC (2009). Cows in farmers’ diet during last 50 days of pregnancy fed lower ME and CP (42.4 MJ and 445 g, respectively) than their daily requirements (43.5 MJ and 519 g, respectively), resulted in lower birth weight of calves compared to improved feeding (13.36 and 15.12 kg, respectively) where daily ME and CP intake was 57.77 MJ and 603 g. In first 60 days of lactation, cows under farmers’ diet fed required amount of ME and CP (44.83 MJ and 471g, respectively) compared to requirement (42 MJ and 388g, respectively). However, cows in improved diet fed 1.28 and 1.42 times higher ME and CP (52.92 MJ and 563 g) than requirements, and produced higher milk (1.97 and 2.50 L/d; P<0.05) and daily gain (122 and 274 g/d; P<0.01), compared to that of farmers’ diet cows. Therefore, it was concluded that diet of RCC cows in late pregnancy may be supplemented with CP in order to produce higher birth weight of calves. In case of lactating cows, a cost effective supplementation of concentrate mixture for increasing milk production and daily gain may be investigated by doing further research. Bangladesh J. of Livestock Res. 21-25: 159-167, 2018